Trabalho em equipe: limites e possibilidades na perspectiva de profissionais de uma equipe de Estratégia Saúde da Família - Dias, Daiane Aparecida (Universidade Federal de São Carlos, 2014)
This study started from an analysis and reflection on Teamwork, from the perspective of professionals from a Family Health Unit (FHU) in a town in the state of São Paulo. The purpose was show the work process, based on the perspective of integrated care, considering the conception of the role of each professional as an integral member of a team, for the production of care. It also shows the vision of these professionals about teamwork, as well as those factors that favors and influence in the relationships established in the work process. The present used a qualitative descriptive-analytical approach to character, whose participants were health professionals, entered a team in the "Strategy of Family Health". Although professionals have noted the importance of interdisciplinary character, its representations indicate that they develop work isolated and fragmented actions. Value the participation of different professions / professionals as team members; however, their representations are not revealing the interaction between their knowledge. It is understood that discussions about teamwork in the context of the family health strategy are crucial to bring about changes in the profile of the various professionals involved, because this implies a collective activity where each member puts their knowledge, feelings ne expectations due to a common objective, that is, in the production of a complete care.
Keywords: Saúde e trabalho; Estratégia saúde da família; Trabalho em equipe; Processo de trabalho; Family health strategy; Teamwork; Work process; CIENCIAS DA SAUDE